A Review of the Intrinsic Parameters Affecting the Elastic Characteristics of Heterogeneous Carbonate Reservoirs: Insights from Laboratory Assessments - Hazaveie, Seyed M.; Aminshahidy, Babak; Nikbin, Mohammad (International Journal of Petroleum Technology, 2024)
This research provides an in-depth analysis of how various parameters such as mineralogy, density, porosity, temperature, pressure, and structural features impact the velocities of sonic waves in carbonate rocks. Our findings reveal that the mineral composition significantly influences the elastic behavior of these rocks. The density and elastic properties of minerals, especially clay minerals, play a crucial role in affecting porosity and predominant pore types. The porosity of carbonate reservoirs impacts their elastic properties, leading to variations in sonic wave velocities depending on the different pore types present. For a given porosity, the velocities can vary considerably due to the presence of diverse pore types within the pore space. Non-interconnected porosities with spherical or near-spherical shapes, along with microporosity, alter the effective elastic properties of the rock. Additionally, temperature affects the velocity-porosity relationship in rocks, with experimental results showing a decrease in P-wave velocity as temperature increases. Under reservoir conditions, wave velocity in carbonate rocks is influenced by factors such as confining pressure, temperature, gas saturation, and effective stress. Specifically, P-wave velocity increases with confining pressure as soft pores and cracks gradually close, enhancing the dry rock bulk shear modulus. Conversely, rising temperatures cause a slight decrease in velocities and an increase in attenuation. In conclusion, this study enhances our understanding of the physical properties and behavior of carbonate rocks under reservoir conditions, thereby contributing to the exploration and production of hydrocarbon resources.